Socio-demographic profile and psychiatric morbidities of suicide attempters: a cross-sectional observation in a tertiary care hospital of Bangladesh (Bangladesh Journal of Psychiatry, 2020)
Suicide is a perplexing phenomenon of taking one’s own life. Reasons behind suicide attempts are also unique. Clinical characteristics of these patients have not been adequately studied from a psychosocial and psychiatric point in Bangladesh. This study was aimed to assess the socio- demographic profile and psychiatric morbidities in suicide attempters. This was a descriptive cross sectional study conducted from May 2017 to September 2017. A total of 101 patients were selected purposively who were admitted following suicide attempt in different departments of Rangpur Medical College Hospital (RMCH). Medical officers in the psychiatry department interviewed them by using a semi-structured questionnaire. Diagnosis was made according to DSM-IV. The results showed that the majority of the respondents were socio-economically deprived young persons. Most (42%) of them were